Cerium oxide nanosheets-based tertiary composites (CeO2/ZnO/ZnWO4) for supercapattery application and evaluation of faradic & non-faradic capacitive distribution by using Donn's model. (30th November 2022) - Khawar, Muhammad Ramzan; Shad, Naveed Akhtar; Hussain, Sajad; Javed, Yasir; Sajid, Muhammad Munir; Jilani, Asim; Faheem, Muhammad; Asghar, Ali
Abstract: Batteries and supercapacitors are trending energy storage devices nowadays but the low energy density of supercapacitors and modest power density of batteries limit their applications for practical usage. Recently a new class of energy storage devices called supercapattery has emerged as an ultimate energy storage device which shows a hybrid storage mechanism of both battery and supercapacitor. In the present work, CeO2 -based binary and tertiary composites have been prepared by the facile hydrothermal method, characterized by different techniques, and applied as an electrode in supercapacitors and supercapattery. The X-ray diffraction patterns and EDX confirm the successful synthesis of tertiary composites with the average crystallite size of 26 nm while the SEM images show the randomly orientated nanosheets of CeO2 loaded with ZnO and ZnWO4 over it. The XPS spectrum depicts the presence of variable oxidation states of cerium (Ce +2 and Ce +4 ) in the tertiary composites. The electrochemical performance shows the highest specific capacity (496.9 Cg −1 ) for tertiary composite. The supercapattery device is fabricated by using mixed (AC/Ternary composite) as a working electrode and AC as a cathode which is separated by filter paper. The evaluation of capacitive and battery mechanisms shows the dominant feature of diffusive and surface-controlled processes at lower and high scan rates respectively due to varying diffusion time of electrolyte species. The fabricated device shows the energy density and power density of 56.92 Whkg −1 and 2000 Wkg −1 at a current density of 0.5 mAg −1 respectively with 88 % cyclic stability and 82 % coulombic efficiency. Graphical abstract: Unlabelled Image Highlights: Synthesis of CeO2 /ZnO/ZnWO4 tertiary composites by hydrothermal method Characterization of materials by XRD, SEM, EDX, XPS etc. Use of tertiary materials as an electrode in supercapattery Energy density and power density of 56.92 Whkg -1 and 2000 Wkg -1 at current density of 0.5 mAg -1 respectively The device has 88% cyclic stability and 82% coulombic efficiency up to 5000 cycles